Production and Certification of Synthetic Selenium Isotopic Reference Materials. Issue 2 (27th July 2015) - Ren, Tongxiang; Wang, Jun; Lu, Hai; Zhou, Tao; Zhou, Yuanjing
Abstract : Due to intensive research into selenium isotopes in recent years, the increasing requirement for reliable and comparable measurement results has created a strong demand for selenium isotopic certified reference materials (iCRM) that were previously not available. To address this, eleven selenium iCRMs were developed, including ten synthetic iCRMs (GBW 04447–GBW 04456) and one natural iCRM (GBW 04457). The synthetic iCRMs were prepared with 76 Se, 78 Se, 80 Se and 82 Se solutions and a natural selenium solution; the natural iCRM was prepared with highly pure selenium material. The property values of isotope ratios in these iCRMs were certified by calibrated mass spectrometry with a collision cell multi‐collector ICP‐MS. The mass discrimination effect of the instrument was corrected with corresponding 78 Se/ 76 Se isotope mixtures and 82 Se/ 76 Se isotope mixtures, which were gravimetrically prepared with purified, isotopically enriched selenium materials. Homogeneity and stability tests were performed, and no significant influences were found. The uncertainty of the property values of the iCRMs was evaluated according to the Guide to the Expression of Uncertainty in Measurement (GUM) of ISO/BIPM and ISO Guide 35. The δ 82/76 Se value of GBW 04457 relative to NIST SRM 3149 was also calculated. These iCRMs are intended for use in calibration of instruments and evaluation of methods for the determination of selenium isotope ratios.